Makna Dakwah Simbolik dalam Ritual Ziarah di Makam Sunan Gunung Jati : Studi Fenomenologi Peziarah - Muhammad Dicky Hasbi Ash-Shiddieqy; Muhammad Ronaydi (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2026)
This study examines the practice of symbolic da’wah in the pilgrimage ritual at the Tomb of Sunan Gunung Jati, Cirebon, with a focus on how pilgrims interpret and construct meanings of symbols. The study aims to analyze pilgrimage ritual symbols as a medium of cultural da’wah communication from a phenomenological perspective. A qualitative phenomenological approach was employed through observation, in-depth interviews, and documentation. Data were collected from five informants consisting of local pilgrims, out-of-town pilgrims, caretakers of the tomb (juru kunci), traders, and tomb managers during the period of January–March 2026.The findings show that symbols such as tahlil, collective prayers, tomb etiquette rules, acts of devotion (khusyuk), and the role of the caretaker are interpreted as media for the internalization of Islamic values in a nonverbal and participatory manner. Social interactions among pilgrims also shape diverse processes of religious meaning-making depending on individual experiences and socio-cultural backgrounds. The study reveals that pilgrimage practices are not only understood as spiritual rituals but also as a space for symbolic da’wah communication embedded within community culture.The novelty of this research lies in its interpretation of pilgrimage as a process of symbolic da’wah communication based on lived social and cultural experiences, rather than merely a religious tradition. Thus, culture has the potential to serve as a contextual and participatory medium of da’wah within Indonesian Muslim society.